2010
DOI: 10.1111/j.1600-0625.2010.01128.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of platinum nanoparticles against UV‐light‐induced epidermal inflammation

Abstract: Intracellular reactive oxygen species (ROS) and apoptosis play important roles in the ultraviolet (UV)-induced inflammatory responses in the skin. Metal nanoparticles have been developed to increase the catalytic activity of metals, which is because of the large surface area of smaller particles. Platinum nanoparticles (nano-Pt) protected by poly acrylic acid were manufactured by reduction with ethanol. A marked increase in ROS production was observed in UV-treated HaCaT keratinocytes cell lines, while a decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 30 publications
0
41
0
Order By: Relevance
“…MC1R variants are associated with red hair, pale skin, freckling and sun sensitivity and have been found to increase CM risk regardless of familiality (8)(9)(10)(11)(12)(13)(14)(15). Furthermore, it has been suggested that MC1R variants may be involved in CM development both via…”
Section: Supporting Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…MC1R variants are associated with red hair, pale skin, freckling and sun sensitivity and have been found to increase CM risk regardless of familiality (8)(9)(10)(11)(12)(13)(14)(15). Furthermore, it has been suggested that MC1R variants may be involved in CM development both via…”
Section: Supporting Informationmentioning
confidence: 99%
“…Ultraviolet (UV) irradiation from sunlight induces various biological effects on the human skin, including skin thickening, wrinkle formation, inflammation, pigmentation, cell death and skin cancer (8,9). It is well-known that ultraviolet B (UVB) stimulates keratinocytes to secrete a large variety of growth factors and cytokines (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…It functions as a physical barrier and protects tissues and internal organs from harmful stimuli. It is well known that UV radiation, in particular UVB (290-320 nm), has adverse effects on human skin, inducing DNA damage (Matsunaga et al, 1991;Matsumura and Ananthaswamy, 2004), skin cancer (Fisher and Kripke, 1982;Gloster and Brodland, 1996;Gerbaudo and Dinisio de Cabalier, 2010), inflammation (Yoshihisa et al, 2010), and apoptosis (Kulms and Schwarz, 2000), which are mediated by generation of reactive oxygen species (ROS). Since skin is frequently exposed to oxidative stress, it is important to know what mechanisms serve to protect the skin cells.…”
Section: Introductionmentioning
confidence: 99%
“…Taking advantage of the unique properties of nano-sized particles, various types of nanomaterials have been designed to aid the transport of diagnostic or therapeutic agents through biologic barriers, target specific molecules, mediate molecular interactions, and detect molecular changes in a sensitive, high-throughput manner 1,2) . Colloidal platinum nanoparticles (CPtN) were recently developed and are currently being evaluated for the ability to reduce inflammation 3,4) , prevent apoptosis 5) , and delay the aging process 6) . As for dental applications, it has been reported that usage of CPtN in combination with a 4-methacryloyloxyethyl trimellitic anhydride (4-META)/methyl methacrylate (MMA) adhesive increases the dentin bond strength to twice that of the parent material, probably due to enhanced polymerization [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%